2019
DOI: 10.1080/09658211.2019.1693598
|View full text |Cite
|
Sign up to set email alerts
|

Predicted and remembered emotion: tomorrow’s vividness trumps yesterday’s accuracy

Abstract: People rely on predicted and remembered emotion to guide important decisions. But how much can they trust their mental representations of emotion to be accurate, and how much do they trust them? In this investigation, participants (N = 957) reported their predicted, experienced, and remembered emotional response to the outcome of the 2016 U.S. presidential election. They also reported how accurate and vivid they perceived their predictions and memories to be, and the importance of the election. Participants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Compared to controls, participants with HSAM showed slightly greater consistency in their memory for emotions associated with low control (upset, distress, sadness, grief) and no difference in the consistency of memory for emotions associated with high control (anger, frustration). Levine et al (2020) found that participants with HSAM did not differ from controls in the accuracy with which they remembered their emotional response to Trump's victory in the 2016 U.S. presidential election after three weeks. Because superior memory may only become apparent in people with HSAM after a longer retention interval, and recognition memory for facts concerning public events had not been tested in this group, we examined memory for facts and feelings concerning the 2016 U.S. presidential election after six months.…”
Section: Highly Superior Autobiographical Memorymentioning
confidence: 82%
See 3 more Smart Citations
“…Compared to controls, participants with HSAM showed slightly greater consistency in their memory for emotions associated with low control (upset, distress, sadness, grief) and no difference in the consistency of memory for emotions associated with high control (anger, frustration). Levine et al (2020) found that participants with HSAM did not differ from controls in the accuracy with which they remembered their emotional response to Trump's victory in the 2016 U.S. presidential election after three weeks. Because superior memory may only become apparent in people with HSAM after a longer retention interval, and recognition memory for facts concerning public events had not been tested in this group, we examined memory for facts and feelings concerning the 2016 U.S. presidential election after six months.…”
Section: Highly Superior Autobiographical Memorymentioning
confidence: 82%
“…Repetition of details via media exposure and rehearsal should promote accuracy in memories of facts but not feelings (Tinti et al, 2014). Consistency over time in participants' feelings and appraisals of political events should promote accuracy in memories of feelings but not facts (Levine et al, 2020). Individuals with HSAM in Study 1 were expected to remember election-related facts, but not their feelings, more accurately than the main group of participants.…”
Section: The Current Investigationmentioning
confidence: 95%
See 2 more Smart Citations
“…One explanation is that memory for past feelings (i.e., Time 1 scores) doesn't differ very much whether the time between the experience of the feelings and the recall of that experience is one day or two-five days. Most studies on memory for past feelings involve much longer periods between experience and recall (e.g., Kaplan et al, 2016;Levine et al, 2020;Levine et al, 2001;Levine et al, 2012;Ottenstein & Lischetzke, 2020;Safer et al, 2002). Thus, empirically, it's unknown how short a delay is required for memory of past feelings to be relatively more accurate.…”
Section: Resultsmentioning
confidence: 99%